Giant cell tumor of the metacarpal bone in children. Issue 1 (January 2015) - Baki, Mehmet Emre; Güvercin, Yilmaz; Yildiz, Mehmet; Aynaci, Osman; Yildiz, Kadriye
<x xml:space="preserve">Abstract</x> We present a successful total resection of metacarpal bone and nonvascularized joint transfer in a giant cell tumor of the fourth metacarpal bone in a 13-year-old girl. At the 6-year follow-up, a good functional outcome was achieved, with 85° range of motion of the metacarpophalangeal joint and no clinical or radiographic evidence of tumor recurrence and no signs of degeneration of the joint.